Involvement of human liver cytochrome P4502B6 in the metabolism of propofol - Oda, Yutaka (Blackwell Science Inc, 2001)
AIMS: To determine the cytochrome P450 (CYP) isoforms involved in the oxidation of propofol by human liver microsomes. METHODS: The rate constant calculated from the disappearance of propofol in an incubation mixture with human liver microsomes and recombinant human CYP isoforms was used as a measure of the rate of metabolism of propofol. The correlation of these rate constants with rates of metabolism of CYP isoform-selective substrates by liver microsomes, the effect of CYP isoform-selective chemical inhibitors and monoclonal antibodies on propofol metabolism by liver microsomes, and its metabolism by recombinant human CYP isoforms were examined. RESULTS: The mean rate constant of propofol metabolism by liver microsomes obtained from six individuals was 4.2 (95% confidence intervals 2.7, 5.7) nmol min(−1) mg(−1) protein. The rate constants of propofol by microsomes were significantly correlated with S-mephenytoin N-demethylation, a marker of CYP2B6 (r = 0.93, P < 0.0001), but not with the metabolic activities of other CYP isoform-selective substrates. Of the chemical inhibitors of CYP isoforms tested, orphenadrine, a CYP2B6 inhibitor, reduced the rate constant of propofol by liver microsomes by 38% (P < 0.05), while other CYP isoform-selective inhibitors had no effects. Of the recombinant CYP isoforms screened, CYP2B6 produced the highest rate constant for propofol metabolism (197 nmol min(−1) nmol P450(−1)). An antibody against CYP2B6 inhibited the disappearance of propofol in liver microsomes by 74%. Antibodies raised against other CYP isoforms had no effect on the metabolism of propofol. CONCLUSIONS: CYP2B6 is predominantly involved in the oxidation of propofol by human liver microsomes.